الرياضيات بالعربية

أوجد النهايات بتغيير المتغير

أوجد النهايات التالية :

$\lim_{x\rightarrow 0} \frac{\sin(\pi x)}{x} $

$\lim_{n \rightarrow \pm \infty} (1+\frac{x}{n})^n$

$\lim_{h \rightarrow 0} \frac{x^h - 1}{h}$
يرجى مراجعة النهايات التالية أولا :حدد النهايات التالية.



$\lim_{x\rightarrow 0} \frac{\sin(\pi x)}{x} $

نضع $X = \pi x$ إذن :

$\lim_{x\rightarrow 0} \frac{\sin(\pi x)}{x} = \lim_{X \rightarrow 0} \pi \frac{\sin(X)}{X} = \pi$

إذن :

${\color{DarkRed} \lim_{x\rightarrow 0} \frac{\sin(\pi x)}{x} = \pi}$



ليكن $x \in \mathbb{R}$.

$\lim_{n \rightarrow \pm \infty} (1+\frac{x}{n})^n = \lim_{n \rightarrow \pm \infty} e^{n \ln(1+\frac{x}{n})}$

ليكن $ x \neq 0$ نضع :

$\epsilon = \frac{x}{n}$

لدينا :

$n \rightarrow \pm \infty \Leftrightarrow \epsilon \rightarrow 0$

$\lim_{n \rightarrow \pm \infty} (1+\frac{x}{n})^n = \lim_{\epsilon \rightarrow 0} e^{x \frac{\ln(1+ \epsilon)}{\epsilon}}$

لتكن : $f(x) = \ln(1+x)$

لدينا :

$\begin{array}{rcl}\displaystyle\lim_{\epsilon \rightarrow 0} \dfrac{\ln(1+ \epsilon)}{\epsilon}& = & \displaystyle\lim_{\epsilon \rightarrow 0} \dfrac{f(0 + \epsilon) - f(0)}{\epsilon - 0} \\ \\~ & = & f^{'} (0) = 1\end{array}$

إذن :

${\color{DarkRed} \lim_{n \rightarrow \pm \infty} (1+\frac{x}{n})^n = e^{x}}$




ليكن $x \in ]0, + \infty[$

$\lim_{h \rightarrow 0} \frac{x^h - 1}{h} = \lim_{h \rightarrow 0} \frac{e^{h \ln(x)} - 1}{h} $

ليكن $x \neq 1$ نضع :

$X = h \, \ln(x)$

إذن :

$\lim_{h \rightarrow 0} \frac{x^h - 1}{h} = \lim_{X \rightarrow 0} \ln(x) \, \frac{e^{X} - 1}{X} $

لدينا :

$ \lim_{X \rightarrow 0} \frac{e^{X} - 1}{X} = 1$

إذن :

${\color{DarkRed} \lim_{h \rightarrow 0} \frac{x^h - 1}{h} = \ln(x)}$